2014
DOI: 10.1007/s11745-014-3886-7
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of the Acyl‐CoA and the Involvement PDAT and DGAT in the Biosynthesis of Erucic Acid‐Rich Triacylglycerols in Crambe Seed Oil

Abstract: The triacylglycerol of Crambe abyssinica seeds consist of 95 % very long chain (>18 carbon) fatty acids (86 % erucic acid; 22:1∆13) in the sn-1 and sn-3 positions. This would suggest that C. abyssinica triacylglycerols are not formed by the action of the phospholipid:diacylglycerol acyltransferase (PDAT), but are rather the results of acyl-CoA:diacylglycerol acyltransferase (DGAT) activity. However, measurements of PDAT and DGAT activities in microsomal membranes showed that C. abyssinica has significant PDAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…Knockout in PDAT did not significantly affect the seed FA composition in Arabidopsis [33,34]. Reports have suggested that activity levels of both PDAT and PDCT are very low in Crambe [34,35], and are thus not expected to significantly influence the FA composition of the seed oil. However, both PDCT-RNAi and PDAT-RNAi lines showed a significant increase in 18:1 and decrease in 18:2, with no major change in 22:1 levels, although the changes were very subtle for the PDAT-RNAi lines.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Knockout in PDAT did not significantly affect the seed FA composition in Arabidopsis [33,34]. Reports have suggested that activity levels of both PDAT and PDCT are very low in Crambe [34,35], and are thus not expected to significantly influence the FA composition of the seed oil. However, both PDCT-RNAi and PDAT-RNAi lines showed a significant increase in 18:1 and decrease in 18:2, with no major change in 22:1 levels, although the changes were very subtle for the PDAT-RNAi lines.…”
Section: Discussionmentioning
confidence: 77%
“…Arabidopsis with knockout of both LPCAT1/2 and PDCT genes led to a further increase in 18:1 over the levels seen in the parents with PDCT or LPCAT1/2 knockout alone [14]. Knockout in PDAT did not significantly affect the seed FA composition in Arabidopsis [33,34]. Reports have suggested that activity levels of both PDAT and PDCT are very low in Crambe [34,35], and are thus not expected to significantly influence the FA composition of the seed oil.…”
Section: Discussionmentioning
confidence: 84%
“…hydroxy, petroselinic, epoxy, conjugated, acetylenic and decanoic acids) in transgenic tissues through either single or multiple gene introductions (Jaworski and Cahoon, 2003;Snapp and Lu, 2013;Carlsson et al, 2014). Diverse research approaches have been utilized in attempts to understand potential difficulies in accumulating these unusual FAs, including: (i) characterizing the enzymes of native species by in vitro assays (Broadwater et al, 2002;Furmanek et al, 2014), (ii) using reverse genetics approaches to enhance or suppress select steps within the targeted pathway (Kumar et al, 2006;Burgal et al, 2008;Li et al, 2010b;Van Erp et al, 2015), (iii) using forward genetics approaches to identify important genes that alter a plant's ability to accumulate a transgenic product (Lu et al, 2006), and (iv) monitoring pathway fluxes through in vivo/in vitro radiolabeling of wild, model and transgenic species (Engeseth and Stymne, 1996;Reed et al, 1997;Bates and Browse, 2011;Bates et al, 2014). Here we have attempted to complement these approaches by transcriptional profiling of two genetically very closely related species [Physaria fendleri (Physaria) and Camelina sativa (Camelina)] to identify differences in lipid metabolism that may have evolved to enable the native Physaria species to accumulate high amounts of HFAs.…”
Section: Discussionmentioning
confidence: 99%
“…In B. napus, there are six paralogs encoding FAE1 proteins (Qiu et al, 2006;Wu et al, 2008;Cao et al, 2010). BnaA8.FAE1 and BnaC3.FAE1 are the two major genes responsible for erucic acid synthesis in B. napus seeds and they elongate 18:1-CoA to 20:1-CoA, and then 20:1-CoA to 22:1-CoA (Furmanek et al, 2014;Kaur et al, 2019). These two genes are highly expressed in the seeds of high-erucic acid varieties and are minimally expressed in low-erucic acid varieties (Qiu et al, 2006;Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%